Measured copper toxicity to Cnesterodon decemmaculatus (Pisces : Poeciliidae) and predicted by biotic ligand model in pilcomayo river wate : a step for a cross-fish-species extrapolation - Casares, María Victoria (2012)
Fil: Weigandt, Cristian Fernando. Universidad de Buenos Aires. Facultad de Agronomía. Buenos Aires, Argentina.